A Hybrid Approach for Managing Low Tongue Posture in Open Bite Using a Composite Habit-Breaking Appliance - Roy , Abhishek Singha; Mandal , Samit; Hamid , Saeed Bin; Rafiq , Shabir (Advanced Concepts in Medicine and Medical Research Vol. 10, 2023)
This chapter describes managing low tongue posture in open bite by a composite habit breaking appliance. Tongue dysfunction in form of altered tongue rest posture and tongue tip protrusion during swallowing, go along with anterior open bite malocclusion in majority of cases. After determining that an aberrant tongue posture is the cause of open bite, orthodontists should categorize tongue posture by examining the morphological characteristics of the malocclusion. Vertical orientation of tongue at any given posture deserves equal consideration to that of its forward thrusting potential. In cases with low tongue rest posture, blocking mechanism such as cribs, may not alone be effective, as it also requires upward elevation of tongue to achieve normal rest posture. On the other hand, tongue stimulator appliances, namely bluegrass appliances and tongue practice beads, as well as myofunctional therapy, require a great deal of patient engagement to become clinically effective in modifying tongue behavior. We endeavour to find therapeutic potential of hybrid approach; that combines forward tongue restriction and vertical elevation via a composite habit breaking appliance (CHBA), in patients having low forward resting posture of tongue. A case report has been presented to exemplify the idea.